PENGARUH KOMPLEKSITAS, KEMANDIRIAN DAN OPINI TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN PEMERINTAH DAERAH DI INDONESIA - Saputra, Yuda; Ariani, Nita Erika (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
This research aims to examine the effect of complexity, local financial independence and opinion either partially and simultaneously towards the timeliness of financial reporting of local government in Indonesia. The samples are collected using census and resulted 542 local government which became a sample. Data used in this research were secondary data in 2015 obtained from BPK and BPS. In order to test the hypothesis, this research used binary logistik regression. The results revealed that (1) complexity, local financial independence, and opinion simultaneously affected timeliness of local government, (2) complexity has a positive influence to the timeliness of local government, (3) local financial independence has a positive influence to the timeliness of local government, and (4) opinion has a positive influence to the timeliness of local government